CYSTO-PROSTATOCELE DUE TO PROSTATIC ABSCESS IN A DOG - Prasad, A Arun; Shafiuzama, Mohd; Simon, M Shiju; Kumar, R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Perineal hernia is a most common surgical condition encountered in intact male dogs when the perineal muscle ruptures allowing rectum, pelvis and or abdominal contents to displace underneath perineal skin. Herniation may be unilateral or bilateral which contains pelvic or retroperitoneal fat, serous fluid, a deviated or dilated rectum, a rectal diverticulum, prostate, urinary bladder or small intestine. Perineal hernia due to retro flexion of urinary bladder is an emergency condition which warrants immediate surgical interventions.
Keywords: CYSTO-PROSTATOCELE; DOG; PROSTATIC ABSCESS